Norwegian Business Professionals´ Need for and Use of English as a Business Lingua Franca (BELF) in Multinational Corporations - Nielsen, Tone Holt (HERMES - Journal of Language and Communication in Business, 2019)
English is now the corporate language of many multinational corporations (MNCs) worldwide. However, when English is used as a shared language resource, a lingua franca, its use may be both fluid and local, and the characteristics of its local use should then be explored. This article therefore investigates English used as a Business Lingua Franca (BELF) in MNCs in Norway through task-based interviews with Norwegian business professionals about their need for and use of BELF. The findings indicate that business professionals need to use it frequently, and for both routine and more complex tasks, like demanding business meetings. While getting the job done was paramount to all, several associated NS-like ‘correct’ usage with ‘professionalism.’ Their BELF use was characterized by local, ‘company speak’, translingual practices and the accommodation of both non-native (NNS) and native (NS) speakers of English, and the ways in which the latter were accommodated displayed a more positive attitude to these interlocutors than has been found in similar studies. This article argues that English used as a corporate language is a complex phenomenon requiring business professionals to have a wide set of communication resources and the ability to use the language flexibly.